Epidural Steroid Injections for Low Back Pain: A Narrative Review - Massimiliano Carassiti; Giuseppe Pascarella; Alessandro Strumia; Fabrizio Russo; Giuseppe Francesco Papalia; Rita Cataldo; Francesca Gargano; Fábio Costa; Michelangelo Pierri; Francesca De Tommasi; Carlo Massaroni; Emiliano Schena; et al. (2021)
Low back pain represents a significant socioeconomic burden. Several nonsurgical medical treatments have been proposed for the treatment of this disabling condition. Epidural steroid injections (ESIs) are commonly used to treat lumbosacral radicular pain and to avoid surgery. Even though it is still not clear which type of conservative intervention is superior, several studies have proved that ESIs are able to increase patients’ quality of life, relieve lumbosacral radicular pain and finally, reduce or delay more invasive interventions, such as spinal surgery. The aim of this narrative review is to analyze the mechanism of action of ESIs in patients affected by low back pain and investigate their current application in treating this widespread pathology.